Implementasi Mekanisme Publish-Subscribe pada Pemantauan Kehadiran Beacon menggunakan Protokol Bluetooth Low Energy - Fikry Juan Aulia; Dany Primanita Kartikasari; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Population growth which always increases every year has an impact on the need for public transportation services. In this case, the role of technology is needed in the needs of public transportation services. Angkot is one type of public transportation service used by many residents and currently, the Malang City government has provided information on public transportation routes on the MediaCentre website. However, the problem that occurs is that there is no direct information at the bus stop. This study builds an angkot system system for bus stops with the aim of making it easier to see the angkot when passing the bus stop. The Bluetooth Low Energy (BLE) protocol is used in this study to be embedded in public transportation in the form of a beacon module. The Message Queue Telemetry (MQTT) protocol is used as a communication protocol between stops, using a cloud brokerage service on cloud.mqtt.com. The tests are limited to only 3 pieces of public transportation at one stop. The results of the system functionality test result in all functionality requirements being met. The results of the response time test for the detection of incoming angkot resulted in the highest average detection of 3 angkot with a scanning time of 0.247563 seconds and the lowest average scanning time of 0.117454 seconds. Another response time test is the time of sending data from the bus stop that supervises the angkot to the next stop with the highest average time on the detection of 2 angkots at once with 0.981685 seconds and the lowest average time at 0.792323 seconds. The result of the distance tester is that the maximum range between public transportation and bus stops is 30 meters